Response of Baby Corn Plants toward Concentration of Granule Zeolite and Duration of Zeolite Soaking in Cow Urine - Dede Kardaya; Arifah Rahayu; Didi Rudiansyah (JURNAL AGRONIDA, 2018)
The study was done to assess the effect of zeolite concentration and time of zeolite soakingin cow urine on the growth and production of baby corn. A factorial completely randomized designwith two factors was used. The first factor was zeolite concentration (0%, 5% and 10%). The secondfactor was soaking time in cow urine (1,2,3 and 4 weeks). Results showed that corn plants treatedwith 0% zeolite (fermented urine) have higher stem circumference, leaves color intensity and highercob weight. Plants that were given a concentration of 5% zeolite produced male flowers late. Theduration of zeolite immersion in cow urine did not significantly affect all observed variables.Keywords: stem circumference, male flowers, baby corn, zeolite